Pedagogical Conditions for Improving Economic Education of Preschool Children Through STEAM-Based Learning Technologies - Boltayeva, Nasiba Ilhom-kizi (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2026)
The rapid development of technology, globalization, and digital transformation has significantly changed the requirements imposed on future generations. Economic literacy is increasingly recognized as an essential life competence that should begin to develop in early childhood. Preschool age represents a critical period during which children acquire foundational knowledge, attitudes, and behaviors that influence their future social and economic participation. Traditional approaches to economic education in preschool settings often focus on isolated concepts such as money recognition, saving, and consumption, while neglecting the development of critical thinking, creativity, problem-solving, and interdisciplinary competencies necessary for modern economic life.STEAM (Science, Technology, Engineering, Arts, and Mathematics) education offers innovative opportunities for integrating economic concepts into meaningful learning experiences. Through project-based activities, experimentation, collaborative learning, and creative problem-solving, STEAM technologies can contribute to the formation of economic awareness and responsible decision-making among preschool children. However, effective implementation requires specific pedagogical conditions that ensure developmental appropriateness, active engagement, and integration of economic content within preschool curricula.This study examines the pedagogical conditions necessary for improving economic education among preschool children through STEAM-based learning technologies. The research employs a qualitative and theoretical approach based on literature analysis, comparative pedagogical review, and synthesis of contemporary studies on early childhood education, economic literacy, and STEAM learning. The findings identify several critical pedagogical conditions, including child-centered learning environments, integration of economic concepts into daily activities, teacher professional competence, family involvement, interdisciplinary project design, and the use of digital and interactive educational resources. The study demonstrates that STEAM-based economic education enhances children's cognitive, social, creative, and economic competencies while promoting sustainable learning outcomes.The article contributes to the growing body of knowledge on early childhood economic education and provides practical recommendations for educators, curriculum developers, and policymakers seeking to improve preschool economic literacy through innovative pedagogical approaches.